2008
DOI: 10.1101/gad.458008
|View full text |Cite
|
Sign up to set email alerts
|

A cryptic unstable transcript mediates transcriptional trans-silencing of the Ty1 retrotransposon in S. cerevisiae

Abstract: Cryptic unstable transcripts (CUTs) are synthesized from intra-and intergenic regions in Saccharomyces cerevisiae and are rapidly degraded by RNA surveillance pathways, but their function(s) remain(s) elusive. Here, we show that an antisense TY1 CUT, starting within the Ty1 retrotransposon and encompassing the promoter 5 long terminal repeat (LTR), mediates RNA-dependent gene silencing and represses Ty1 mobility. We show that the Ty1 regulatory RNA is synthesized by RNA polymerase II, polyadenylated, and desta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
212
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 179 publications
(225 citation statements)
references
References 57 publications
(68 reference statements)
11
212
2
Order By: Relevance
“…55,56 The generality of ncRNAs modulating transcription from promoters in their immediate vicinity is unknown, but these results suggest that DNA associated RNAs can be the targets of RNA binding proteins which interact with chromatin modifying enzymes and lead to changes in gene expression level.…”
Section: Possible Functions Of Divergent Rnasmentioning
confidence: 99%
“…55,56 The generality of ncRNAs modulating transcription from promoters in their immediate vicinity is unknown, but these results suggest that DNA associated RNAs can be the targets of RNA binding proteins which interact with chromatin modifying enzymes and lead to changes in gene expression level.…”
Section: Possible Functions Of Divergent Rnasmentioning
confidence: 99%
“…21,22 In addition, mutations resulting in C-terminal truncation of Gag an approach alternative to Gag-p49 induction, we examined the ability of tagTy1 to form T-bodies in the xrn1Δ strain. We chose this background due to the strong inhibition of Ty1 transposition in the absence of the Xrn1p exonuclease, 17 probably due to the accumulation of Ty1 antisense RNAs that inhibit VLP maturation. 17,18 Consistent with a previous report in reference 2, we observed significantly decreased T-body counts in xrn1Δ cells transformed with an empty vector (Fig.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…We chose this background due to the strong inhibition of Ty1 transposition in the absence of the Xrn1p exonuclease, 17 probably due to the accumulation of Ty1 antisense RNAs that inhibit VLP maturation. 17,18 Consistent with a previous report in reference 2, we observed significantly decreased T-body counts in xrn1Δ cells transformed with an empty vector (Fig. 4).…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…Heterochromatic gene silencing has been most extensively described in Schizosaccharomyces pombe, where siRNAs originating from these regions target the RITS complex to induce repressive histone modifications (Volpe et al 2002; for review, see Buhler and Moazed 2007). Although, the complete RNAi machinery is absent in Saccharomyces cerevisiae (Aravind et al 2000), RNA-mediated TGS within euchromatin has been recently reported (Camblong et al 2007;Berretta et al 2008;Houseley et al 2008). In particular, we showed that stabilization of PHO84 antisense RNAs, escaping degradation by the nuclear exosome in the absence of the Rrp6 exoribonuclease or during chronological aging, leads to PHO84 TGS via a mechanism implicating the Hda1/2/3 histone deacetylase (Camblong et al 2007).…”
mentioning
confidence: 99%